Facile Synthesis of Wide-Bandgap Fluorinated Graphene Semiconductors - Chang, Haixin; Cheng, Jinsheng; Liu, Xuqing; Gao, Junfeng; Li, Mingjian; Li, Jinghong; Tao, Xiaoming; Ding, Feng; Zheng, Zijian (Chemistry : a European journal, 2011)
The bandgap opening of graphene is extremely important for the expansion of the applications of graphene‐based materials into optoelectronics and photonics. Current methods to open the bandgap of graphene have intrinsic drawbacks including small bandgap openings, the use hazardous/harsh chemical oxidations, and the requirement of expensive chemical‐vapor deposition technologies. Herein, an eco‐friendly, highly effective, low‐cost, and highly scalable synthetic approach is reported for synthesizing wide‐bandgap fluorinated graphene (F‐graphene or or fluorographene) semiconductors under ambient conditions. In this synthesis, ionic liquids are used as the only chemical to exfoliate commercially available fluorinated graphite into single and few‐layer F‐graphene. Experimental and theoretical results show that the bandgap of F‐graphene is largely dependent on the F coverage and configuration, and thereby can be tuned over a very wide range. Fluorinated graphenes: An eco‐friendly, highly effective, low‐cost, and highly scalable approach has been developed to synthesize wide‐bandgap fluorinated graphene (F‐graphene; see figure) semiconductors. Experimental and theoretical results show the F‐graphene bandgaps are largely dependent on the F coverage and configurations, and can be tuned over a very wide range.